Design of a novel shunt active harmonic compensator with AUV-PQ-SRF reference current extraction, OSV-MPC and SMC techniques - Kumar Reddy Cheepati; E. Parimalasundar; K. Suresh; Marco Rivera; M. Nageswara Rao; Aravind Pitchai (Scientific Reports)
Abstract Harmonic distortion makes it difficult to maintain good Electrical Power Quality (EPQ) in distribution networks with many nonlinear loads. Three significant advances are combined in this paper’s innovative Shunt Active Harmonic Compensator (SAHC) design: (i) a new technique for extracting reference currents, called AUV-PQ-SRF, which combines the Unit Vector, PQ, and SRF techniques in a unique way to improve harmonic detection; (ii) an OSV-MPC strategy that improves reference current tracking accuracy by doing away with traditional pulse width modulation; and (iii) a Sliding Mode Controller (SMC) for dynamic and reliable DC link voltage regulation under a range of load conditions. The accuracy, robustness, and response time issues with traditional methods are addressed by the suggested approach. Results from simulations conducted in accordance with IEEE-519-2022 standards show a considerable decrease in total harmonic distortion (THD), along with increased power factor and real and reactive power compensation. This study provides a thorough and useful solution for dynamic power quality issues, setting a new standard in active filtering.